Lost in Familiar Places: Creating New Connections Between the Individual and SocietyLost in Familiar Places: Creating New Connections Between the Individual and Society, by ShapiroEdward R. and CarrA. Wesley. New Haven, CT: Yale University Press, 1991, 193 pp., $21.25, cloth. - Kahn, William A. (Academy of Management Review, 1992)
This article presents a review of the book ?Lost in Familiar Places: Creating New Connections Between the Individual and Society,? by Edward Shapiro and A. Weslev Carr.